Depression, anxiety, and stress levels during the COVID-19 pandemic: A longitudinal study among Indonesian psychologists - Fitri Ariyanti Abidin; Ahmad Gimmy Prathama; Efi Fitriana; Anggi Mayangsari; Rahmi Salsabila Putri Syam; Sophia Amira Latifa Hakim; Joeri K. Tijdink (PLoS ONE, 2025)
During the COVID-19 pandemic, while clinical psychologists played a crucial role in supporting mental health, their well-being was overlooked compared to other healthcare professionals. Therefore, this study aimed to examine the trend levels of depressive symptoms, anxiety, and stress among psychologists during the pandemic and explore how these levels are related to demographic characteristics, personality traits, and self-compassion. One hundred and ten psychologists who provided online counseling during the pandemic participated in all three-time points of the study conducted from January to October 2021 in the midst of the pandemic. The validated Indonesian versions of the DASS-21, Big Five Personality, and Self-Compassion Scale were surveyed. The results indicated that despite no significant longitudinal changes in stress, anxiety, and depression levels (p > 0.05) over nine months, the prevalence of moderate-to-severe depressive symptoms, anxiety, and stress was noted in 10.9%−14.5%; 22.7%−30.9%; and 11.8%−14.5%; respectively. In terms of protective and risk factors, being married, older age, higher openness to experience, higher extraversion, and higher conscientiousness emerged as potential protective factors against mental health issues. Additionally, self-compassion was linked to depression, anxiety, and stress at corresponding time points; however, its impact diminished over time. Meanwhile, stress emerged as a significant predictor of both depression and anxiety. These findings demonstrate that the mental health of psychologists during the pandemic was not severely affected over time. Compared with other populations, the levels of depressive symptoms, anxiety, and stress are lower. The results may indicate that Indonesian psychologists are able to cope with very stressful situations, like a global pandemic. Future studies should focus on protective factors.